2007
DOI: 10.1007/s10552-007-9012-x
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population

Abstract: Objectives-Methylenetetrahydrofolate reductase (MTHFR), which is expressed in the liver, may be involved in both DNA methylation and DNA synthesis. It is also indicated as a potential risk factor of liver cancer in patients with chronic liver disease. To date, no study has been conducted on MTHFR and hepatocellular carcinoma (HCC) using a population-based design. The objective of this study was to evaluate the effects of polymorphisms of the MTHFR gene on the risk of primary liver cancer and their possible eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 32 publications
3
24
2
Order By: Relevance
“…However, in some groups of Northern Chinese [42,43], the 677T allele was more common than the 677C allele. In this study, the frequency of the 677T allele was most frequent in Chinese (27.5%), which was lower than the frequencies in other Chinese populations (30.7 to 44.6%) reported before [44][45][46][47][48]. In Singaporean Indians, the frequency of the 677T allele was 12.2%, being similar to the frequencies in Asian Indians living in South Africa (11%) [39] and UK (15.0%) [40], and to the frequency in Malays (10.6%) of this study.…”
Section: Discussioncontrasting
confidence: 83%
“…However, in some groups of Northern Chinese [42,43], the 677T allele was more common than the 677C allele. In this study, the frequency of the 677T allele was most frequent in Chinese (27.5%), which was lower than the frequencies in other Chinese populations (30.7 to 44.6%) reported before [44][45][46][47][48]. In Singaporean Indians, the frequency of the 677T allele was 12.2%, being similar to the frequencies in Asian Indians living in South Africa (11%) [39] and UK (15.0%) [40], and to the frequency in Malays (10.6%) of this study.…”
Section: Discussioncontrasting
confidence: 83%
“…The results in the present study are different in some ways from those observed in 2 previous studies, performed one in an European population (Saffroy et al, 2004) and another in a Chinese population (Mu et al, 2007). In the former, an association was detected between the MTHFR SNP and the occurrence of HCC only in patients with end stage liver disease of alcoholic origin, but not in patients with HCC arisen in cirrhosis of viral origin or in noncirrhotic livers.…”
Section: Discussioncontrasting
confidence: 99%
“…Not surprisingly, therefore, the relationship between MTHFR C677T SNP and the occurrence of malignant diseases has been explored in leukemia (Franco et al, 2001;Robien and Ulrich, 2003;Skibola et al, 1999), stomach (Boccia et al, 2008), colon (Ma et al, 1997;Sharp and Little, 2004;Slattery et al, 1999), breast (Beilby et al, 2004), and bladder (Lin et al, 2004) cancer. Two studies in patients with HCC have yielded conflicting results (Mu et al, 2007;Saffroy et al, 2004).…”
mentioning
confidence: 99%
“…Based on the inclusion criteria, five case-control studies from four publications were included in this meta-analysis (Mu et al, 2007;Yuan et al, 2007;Kwak et al, 2008;Cui et al, 2012) and 21 studies were excluded. The flow chart for the study selection is summarized in Figure 1.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%